The entrepreneur profile of tenants of Independência Shopping Centerin Santa Maria-RS in the management of their projects - Zajonz, Bruna Tadielo; Schulz, Jéferson Réus da Silva; Fenner, Marta; Dörr, Andrea Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The individual microentrepreneur is self employed and legalized as a small businessman. It is perceived that this is a fast growing business category in Brazil as new autonomous business opportunities raise in the country. The aim of this article is to analyze and describe the enterprise profile of microentrepreneur individuals at Independência Shopping Centre in Santa Maria-RS-Brazil, also addressing variables that may characterize the ways in which microentrepreneur run their enterprises. The methodology utilized in this research was based on primary data gathered by means of questionnaire assessment applied to store owners from the 4th to 9th November 2013. Results indicate that there was an income reduction due to an increase in costs after MEI. The data reveals that the majority of microentrepreneurs use the booklet method for financial control whereas others do not apply any control at all. It was concluded that a very few of the microentrepreneurs need financing and those who do need financial support find difficulties to actually get it. It turns out that products commercialized in the Shopping Centre come from different countries or cities, where prices are generally smaller and microentrepreneurs may ultimately resell them for higher prices.